2005
DOI: 10.1021/jf058057y
|View full text |Cite
|
Sign up to set email alerts
|

Separation, Characterization, and Quantitation of Phenolic Acids in a Little-Known Blueberry (Vaccinium arctostaphylos L.) Fruit by HPLC-MS

Abstract: The aim of this study was the qualitative and quantitative determination of free, ester, glycoside, and ester-bound phenolic acids in the blueberry (Vaccinium arctostaphylos L.) fruit. A method for the determination of the profile of phenolic acids of four different phenolic fractions in the fruit was developed using high-performance liquid chromatography-mass spectrometry (HPLC-MS). Thirteen compounds (gallic, protocatechuic, p-hydroxybenzoic, m-hydroxybenzoic, gentisic, chlorogenic, p-coumaric, caffeic, feru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(60 citation statements)
references
References 39 publications
0
60
0
Order By: Relevance
“…(Häkkinen and Törrönen, 2000;Taruscio et al, 2004;Ayaz et al, 2005). Vaccinium leaf and stem phenolics have received less attention.…”
Section: Discussionmentioning
confidence: 99%
“…(Häkkinen and Törrönen, 2000;Taruscio et al, 2004;Ayaz et al, 2005). Vaccinium leaf and stem phenolics have received less attention.…”
Section: Discussionmentioning
confidence: 99%
“…The phenolic acid fractions were analyzed as described previously [16]. Briefly, internal standards of deuterium-labeled salicylic and p-hydroxybenzoic acids were added to each fraction to a final concentration of 10 …”
Section: Determination Of Phenolics By Hplc-msmentioning
confidence: 99%
“…According to the literature, Ayaz reported that thirteen phenolic compounds were identified in u n c o r r e c t e d p r o o f V. arctostaphylos fruits from Turkey including gallic, protocatechuic, p-hydroxybenzoic, mhydroxybenzoic, gentisic, sinapic, chlorogenic, p-coumaric, ferulic, syringic, caffeic, salicylic and trans-cinnamic acids (14). Saral reported that total phenolic contents of ME of V.…”
Section: Discussionmentioning
confidence: 99%